Preoperative computed tomography and serum α-fetoprotein to predict microvascular invasion in hepatocellular carcinoma. Issue 27 (July 2018) - Zhang, Wei; Liu, Lijuan; Wang, Peng; Wang, Lili; Liu, Lidong; Chen, Jie; Su, Danke
Abstract : Abstract: To determine the diagnostic value of computed tomography (CT) for prediction of microvascular invasion (MVI) in hepatocellular carcinoma (HCC). Preoperative CTs for 160 patients with 57 MVI-positive and 103 MVI-negative HCCs diagnosed by surgical pathology were reviewed retrospectively. CT parameters and serum α-fetoprotein (AFP) level were analyzed in SPSS 16.0. Although univariate analysis showed that tumor size ( P = .012), grade (Z = −2.114, P = .034), and peritumoral enhancement (χ 2 = 4.464, P = .035) were associated with MVI, multiple logistic regression analysis showed that capsular invasion (odds ratio [OR] = 23.469, P < .001), margins (OR = 6.751, P < .001), and serum AFP level (OR = 1.001, P = .038) were associated with MVI in HCC ( P < .05). Radiographic hepatic capsular invasion and nonsmooth tumor margins identified by preoperative CT images, along with AFP levels greater than 232.2 ng/mL, are important predictors of MVI.